Os efeitos da ambidestria na relação entre estresse de papel e desempenho com vendas - Rosa, Marco Aurélio Garcia (2015)
The capacity of a salesperson to cope with apparently antagonistic activities may result in better sales results. This competence is called ambidextrous behavior and is frequently imposed by the environment. An ambidextrous management makes the salesperson struggle for scarce resources to fulfill conflicting goal, allowing and encouraging him to use his own judgment to determine how to apply these resources. This research is aimed at studying ambidexterity on a salesperson individual level, leading them to deal simultaneously with sales activities and service activities. The hypotheses were formulated considering that the characteristics of an ambidextrous behavior favor sales results. On the other hand, role stress dimensions were considered (conflict, ambiguity and excessive workload) as factors causing negative effects on the salesperson's results. Role stress can be defined as a permanent state of mental effort which results in psychological tension that affect an individual's performance. At first the hypothesis that there is and moderation effect of the ambidextrous behavior in relation to role stress (conflict, ambiguity and excessive workload) and results (sales performance, job satisfaction and efficiency). After that mediation hypotheses of ambidextrous behavior in relation to role stress and results were created. The study sample was 307 bank managers from the cities of Maringá and Londrina. The results pointed out that ambidextrous behavior relates positively to job satisfaction and sales performance, as predicted, and also to efficiency. The findings indicate that the dimensions of role stress possess a direct and relevant effect on the sales results, although there was no moderation effect found for the interaction between ambidextrous behavior and stress which caused a significative effect on the result. Aditional analisys of moderation were conducted and finally mediation effects for the hypothised relations were found.